Kidner procedure on symptomatic accessory navicular: a case report - Aryana, I. Gusti Ngurah Wien; Dwi Yudistira, I. Made Arditya (International Journal of Research in Medical Sciences, 2020)
Accessory navicular bone (ANB) is present in 4-20% of the general population. It can cause of midfoot pain and consequently may lead to flat foot. The patient usually presents with pain and swelling on the medial aspect of the foot with difficulty on walking. Diagnosis is often delayed. We report a case of symptomatic accessory navicular on a 30 years old female patient who complained of pain in the medial area of left foot for 2 years, and the pain getting worse in the last 2 weeks. Accessory navicular bone treatment may be non-surgical or surgical treatment in order to improve the symptoms. The following may be used: immobilisation by plaster splint, use of boots when walking, which allow the affected area to rest and reduce inflammation, use of an ice bag covered with a thin towel applied on the affected area in order to reduce swelling, oral non-steroidal anti-inflammatory drugs (NSAID). Surgical treatment of this condition involves removing the accessory bone (this additional bone is not necessary for normal foot function), remodeling the area, and repairing the posterior tibial tendon to improve its function. The most commonly used procedure to treat the symptomatic accessory navicular is Kidner procedure. The accessory navicular is a commonly occurring deformity that, because of its significant accompanying pathomechanical considerations, is closely associated with the pathologic flexible flatfoot. By recognizing and treating this progressive, debilitating deformity, both conservatively and surgically, the astute practitioner will be able to resolve discomfort, improve dysfunction, and restore quality of life.